Taxonomic review of Chinese species of ground beetles of the subgenus Pseudoophonus (genus Harpalus) (Coleoptera: Carabidae) - Kataev, Boris M.; Liang, Hongbin (Zootaxa, 2015)
A taxonomic review of 23 species of the subgenus Pseudoophonus Motschulsky, 1844, the genus Harpalus Latreille, 1802, occurring in China is given, and a key to these species is provided. The species are divided in three species groups and five subgroups, the distinctive characters of which are listed. The following new synonyms are established: Harpalus calceatus Duftschmid, 1812 = Anisodactylus propinquus Ballion, 1870, syn. n.; H. davidi (Tschitschérine, 1897) = H. kailiensis Huang, 1992, syn. n.; = H. adenticulatus Huang, 1992, syn. n.; = H. cilihumerus Huang, Hu & Sun, 1994, syn. n.; H. fokienensis Schauberger, 1930 = H. muciulus Huang, 1992, syn. n.; H. griseus (Panzer, 1796) = H. xinjiangensis Huang, Hu & Sun, 1994, syn. n.; H. hauserianus Schauberger, 1929 = H. disaogashimensis Huang, 1995, syn. n.; H. pastor pastor Motschulsky, 1844 = H. penglainus Huang, Hu & Sun, 1994, syn. n.; = H. chiloschizontus Huang, 1995, syn. n.; H. rufipes (DeGeer, 1774) = H. scabripectus Huang, Hu & Sun, 1994, syn. n.; H. singularis Tschitschérine, 1906 = H. chengjiangensis Huang, 1993, syn. n.; H. sinicus Hope, 1845 = H. periglabellus Huang, 1992, syn. n.; = H. longihornus Lei & Huang, 1997, syn. n.; and H. tridens Morawitz, 1862 = H. hypogeomysis Huang, 1993, syn. n.; = H. pilosus Huang, 1995, syn. n. Statuses of H. yinchuanensis Huang, 1993 and H. disimuciulus Huang, Lei, Yan & Hu, 1996 are discussed. Lectotypes are designated for H. capito Morawitz, 1862, H. japonicus Morawitz, 1862 and H. eous Tschitschérine, 1901. New data on distribution of Pseudoophonus species in China are provided. Harpalus babai Habu, 1973 is reported from China (Jiangxi) for the first time. The following taxa are recorded from the following Chinese provinces for the first time: H. ussuriensis Chaudoir, 1863 from Hunan; H. aenigma (Tschitschérine, 1897) from Hubei, Jiangxi, and Guangxi; H. pastor Motschulsky, 1844 from Beijing and Xizang; H. fokienensis Schauberger, 1930 from Anhui and Jiangxi; H. simplicidens Schauberger, 1929 from Beijing, Shanghai, and Fujian; H. coreanus (Tschitschérine, 1895) from Anhui, Henan, Zhejiang, Shanghai, Hubei, and Guangdong; H. suensoni Kataev, 1997 from Yunnan; H. sinicus Hope, 1845 from Hainan; H. davidi (Tschitschérine, 1897) from Zhejiang, Hunan, and Guizhou; H. pseudohauserianus Kataev, 2001 from Sichuan; H. indicus orientalis Kataev, 2014 from Xizang, Guangxi, and Guangdong; H. hauserianus Schauberger, 1929 from Xizang and Guizhou; H. singularis Tschitschérine, 1906 from Taiwan; and H. calceatus Duftschmid, 1812 from Guangxi. In addition, H. sinicus and H. singularis are reported from Laos for the first time.